Construction of a biocompatible and antioxidant multilayer coating by layer-by-layer assembly of -carrageenan and quercetin nanoparticles - Souza, M. (2018)
The present work aimed at the construction and characterization of a multilayer coating based on -carrageenan and quercetin-loaded lecithin/chitosan nanoparticles (Np) by the layer-by-layer technique and the evaluation of its antioxidant capacity and potential cytotoxicity in vitro. The multilayered coating was successfully self-assembled, as confirmed by UV-Vis spectroscopy, contact angle, atomic force microscopy (AFM), and scanning electron microscopy (SEM). Multilayered coatings showed to have antioxidant capacity, with a DPPH radical scavenging activity of 31.32±3.13% and a result of the FRAP assay of 799.41±95.39 M of ferrous ion (Fe2+) equivalent. These coatings were also shown to be devoid of cell toxicity, as evaluated by determination of nitric oxide production and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) test. The alveolar macrophages culture was tested in the presence of the -carrageenan/quercetin-Np multilayer coating and showed a cell viability of 91.3±9.6%. These results suggest that this multilayered coating is adequate for surfaces modification in view of biomedical and food industry applications.